New Ultrasonic Tip Decreases Uninstrumented Surface and Debris in Flattened Canals: A Micro-computed Tomographic Study - Santos-Junior, Airton Oliveira [UNESP]; Tanomaru-Filho, Mario [UNESP]; Pinto, Jader Camilo [UNESP]; Medina Carita Tavares, Karina Ines [UNESP]; Barreto Pivoto-Joao, Mariana Mena [UNESP]; Guerreiro-Tanomaru, Juliane Maria [UNESP] (Elsevier B.V., 2020)
Introduction: The preparation of flattened root canals using reciprocating or rotary nickel titanium instruments associated with the Flatsonic ultrasonic tip (Helse Ultrasonic, Santa Rosa de Viterbo, SP, Brazil) was evaluated by micro computed tomographic imaging. Methods: Twenty-four flattened distal canals of mandibular molars with a buccolingual diameter 4 or more times larger than the mesiodistal diameter were selected. The root canals were randomly divided into 2 experimental groups for preparation: a Reciproc Blue (RB; VDW GmbH, Munich, Germany) 40/.06 file in reciprocating motion or ProDesign Logic (PDL; Easy Equipamentos Odontologicos, Belo Horizonte, MG, Brazil) 40/.01 and 40/.05 files in rotary motion (n = 12). A complementary preparation was performed with the Flatsonic ultrasonic tip for both preparations. Micro computed tomographic scanning at a resolution of 8.74 mu m was performed before and after preparation with the nickel-titanium instruments and after the use of the Flatsonic tip. The percentages of increase in volume, debris, and uninstrumented surface were analyzed. The data obtained were submitted to the paired and unpaired t test, analysis of variance, and the Tukey test (alpha = 5%). Results: The percentage increase in volume, debris, and uninstrumented surface was similar between RB and PDL in the entire root canal (P>.05). The PDL promoted a lower percentage of debris in the cervical third and a lower percentage of increase in volume in the apical third in comparison with RB (P<.05). The Flatsonic decreased debris and uninstrumented surface after PDL preparation in all thirds (P<.05). After preparation with RB, the Flatsonic decreases the debris in the cervical third and the uninstrumented surface in the cervical and middle thirds (P<.05). Conclusions: The preparation of flattened root canals using RB or PDL produced a high percentage of debris and uninstrumented surface. The Flatsonic ultrasonic tip significantly improved the cleaning of flattened root canals.
Keywords: Micro computed tomography; nickel-titanium; root canal preparation; ultrasonics